Ação da terapia laser de baixa potência nos efeitos deletérios da isquemia em rins destinados a transplante: um estudo pré-clínico - Messias, Felipe de Moura (2012)
Introduction. Acute Kidney injury (AKI) is associated with a high degree of morbidity and mortality. Ischaemia-reperfusion injury (IRI) is one of the major causes of AKI. Currently, inflammatory cytokines specially TNF-α, seems to be involved in the injury and no pharmacological agents have proven to prevent AKI after IRI. In the last decade we demonstrated that LLLT is able to inhibit inflammatory markers including cytokines (TNF-α and IL-1 for example). Aims. Here we investigate the effect of LLLT on inflammatory cytokines in Rat kidney after prolonged ischemia. Methods. After approval of the Ethical Committee for Animal Use, Male Wistar rats were taken to the experiment table and anaesthetized with ketamine plus xilazyne. The anterior abdominal wall was incised on the median line. Both kidneys were excised and immediately placed in cold nutritive solution. Treated groups received laser therapy with 1,3,6 and 10 Joules of energy in different times. After 2, 12 and 24 hours the kidneys were fixed for histological and biochemical analysis. In the laser treated group, an energy dose of 3 Joules was delivered in two points centrally and bilaterally, 5 min after reperfusion. Results. Biochemical analysis revealed no significant alterations for inflammatory cytokines after LLLT. Morphological evaluation demonstrated a better cell organization in the laser-treated groups. Conclusion. Our results demonstrated that LLLT was able to preserve the renal tissue from ischemia-induced lesions.